CHILD-FRIENDLY SCHOOL MANAGEMENT IN ACHIEVING QUALITY EDUCATIONAL SERVICES IN ELEMENTARY SCHOOLS IN DEWANTARA DISTRICT - Fauziah, Fauziah; Yanti, Hera; Dewi, Silvi Listia (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
In improving the quality of educational services, all schools must implement the Child-Friendly School (SRA) program. Thus, we can see the extent of the role of Child-Friendly Schools (SRA) in improving the quality of educational services at the elementary school level. The purpose of this study is to analyze the management of child-friendly schools (SRA) implemented in improving the quality of educational services in elementary schools in Dewantara sub-district, analyze the quality of educational services in elementary schools that can achieve effective child-friendly schools, identify the impacts that occur from child-friendly school management on the quality of educational services, identify supporting factors and inhibiting factors in the implementation of child-friendly school management (SRA). This study uses a qualitative research method using a descriptive approach with the research object of SD Negeri 3 Dewantara and SD Negeri 12 Dewantara, through observation, interview and documentation data collection procedures. The results of the discussion discuss planning, organizing, implementing, and supervising, as well as supporting factors and inhibiting factors in implementing the Child-Friendly School (SRA) program at SD Negeri 3 Dewantara and SD Negeri 12 Dewantara..